Anticoagulant treatment in patients with pulmonary arterial hypertension associated with systemic sclerosis: More shadows than lights. Issue 1 (February 2018) - Palazzini, Massimiliano; Manes, Alessandra; Gotti, Enrico; Dardi, Fabio; Rinaldi, Andrea; Galiè, Nazzareno
Pulmonary arterial hypertension is a chronic and progressive disease characterized by elevated pulmonary artery pressure and pulmonary vascular resistance leading to heart failure and premature death. Pulmonary arterial hypertension is characterized by proliferative and obstructive lesions in the distal pulmonary arteries and some descriptions include also thrombotic lesions. Despite this, in an era when multiple effective pulmonary arterial hypertension therapies are available, the role of anticoagulation in the treatment of pulmonary arterial hypertension remains uncertain. In particular, anticoagulant treatment in pulmonary arterial hypertension associated with connective tissue disease seems to be associated with unfavorable risk to benefit ratio due to an increased rate of bleeding from the gastrointestinal tract. However, anticoagulation may be required in conditions with increased thrombophilia like in the presence of lupus anticoagulant phenomenon or in the presence of anticardiolipin antibodies.